Utilization of Google Earth Engine and DSAS to Monitor Coastal Change in the Banyuasin Estuary - Heron Surbakti; Raisyah Salsabilah; Riris Aryawati; Isnaini; Robinson Sitepu (Jurnal Penelitian Pendidikan IPA, 2025)
This study examines shoreline dynamics in the Banyuasin Estuary, South Sumatra, Indonesia, by integrating multi-decadal satellite imagery (1989-2019) with field-based sedimentation measurements. The research employs Google Earth Engine (GEE) for satellite data processing, FES 2014 tidal corrections to address tidal variations, and the Digital Shoreline Analysis System (DSAS) for precise shoreline change analysis. The primary objective is to comprehensively understand coastline shifts and sediment deposition in stabilising coastal zones. The findings reveal significant shoreline accretion, with net accretion of 2,012 hectares and prominent shoreline advancements at Anakan Island (2,012.33 meters, 118.98 meters/year), while regions such as Sembilang National Park and southern Payung Island exhibited notable erosion (322.71 meters, 10.8 meters/year). The Banyuasin River estuary shifted from notable to extreme accretion phases, contrasting with the more stable shoreline dynamics in the Musi River estuary, where accretion remained stable to intense. The integrated methodology, combining GEE, tidal corrections, and DSAS, offers an innovative approach to monitoring shoreline changes. These findings provide valuable insights for developing sustainable coastal management strategies, particularly in areas facing the dual challenges of climate change and human-induced pressures.